Outflow Cannula Systolic Slope in Patients With Left Ventricular Assist Devices: A Novel Marker of Myocardial Contractility. Issue 2 (February 2019) - Grinstein, Jonathan; Kruse, Eric; Sayer, Gabriel; Kim, Gene H.; Raikhelkar, Jayant; Kalantari, Sara; Sarswat, Nitasha; Adatya, Sirtaz; Ota, Takeyoshi; Jeevanandam, Valluvan; Mor-Avi, Victor; Lang, Roberto M.; et al.
Abstract : Left ventricular (LV) unloading with a LV assist device (LVAD) reverse remodels the heart and may lead to favorable changes in cellular architecture and LV geometry promoting myocardial recovery. Currently, there are no standardized methods for evaluating myocardial recovery. This study assesses the systolic slope of the LVAD outflow cannula as a marker for myocardial contractility. Doppler echocardiography (transthoracic echocardiogram [TTE]) of the LVAD outflow cannula and TTE of the LV cavity were prospectively collected in 57 patients with LVADs. Systolic acceleration of the LVAD outflow cannula was measured in each patient as the peak change of velocity over time (dv/dt) during systole from continuous-wave Doppler signal acquired from the LVAD outflow cannula. Ventricular volumes were concurrently measured by TTE. In a subset of 10 patients, the systolic slope was measured during each stage of a ramp study to study the properties of this parameter across a variety of loading conditions. The systolic slope of the LVAD outflow cannula was successfully measured in 53 of 57 patients (93%). Systolic slope strongly correlated with ejection fraction (EF) ( R = 0.92). Analysis of systolic slope stratified by EF (EF >30%, EF 20–30%, EF 10–20%, and EF <10%) revealed systolic slopes that were significantly different between the groups (1, 371 cm/s 2 ± 324; 983 cm/s 2 ± 122; 578 cm/s 2 ± 139; and 495 cm/s 2 ± 107, respectively; p < 0.001). Systolic slope did not change significantly across variable preload and afterload conditions during a ramp study. Systolic slope of the LVAD outflow cannula strongly correlates with EF and can be used to assess underlying myocardial contractility across a variety of LVAD loading conditions.